2006
DOI: 10.1590/s1519-69842006000300013
|View full text |Cite
|
Sign up to set email alerts
|

Terrestrial passerines in an Atlantic forest remnant of Southern Brazil

Abstract: AbstrActmicrohabitats of four terrestrial passerines were studied in an Atlantic forest remnant of southern Brazil, in two areas (northern and southern) of the mata dos Godoy state Park (PG). Grallaria varia and Hylopezus nattereri showed low abundance and occurred in only one PG area, while Chamaeza campanisona and Corythopis delalandi were recorded in two. The microhabitats of C. campanisona, G. varia, and H. nattereri had many large trees and a dense understory. Corythopis delalandi was in areas having few … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 19 publications
0
2
0
1
Order By: Relevance
“…The increase of food supply does not seem to be so high in the Apertados river as in Alaska, but certainly ground invertebrates could be benefited with the humidity and could have their abundance increased. The bird guild that could benefit most from increased invertebrate abundance is the ground omnivores (VOLPATO et al 2006); that guild had almost the twice the number of contacts along the riparian trails (167) compared to the upland ones (90).…”
Section: Discussionmentioning
confidence: 99%
“…The increase of food supply does not seem to be so high in the Apertados river as in Alaska, but certainly ground invertebrates could be benefited with the humidity and could have their abundance increased. The bird guild that could benefit most from increased invertebrate abundance is the ground omnivores (VOLPATO et al 2006); that guild had almost the twice the number of contacts along the riparian trails (167) compared to the upland ones (90).…”
Section: Discussionmentioning
confidence: 99%
“…As espécies de aves que apresentaram maior valor de IPA em CB2 têm sido mais frequentemente associadas a agrupamentos de bambu do interior de floresta, como Drymophila rubricollis, Conopophaga lineata, Hylopezus nattereri, Synallaxis cinerascens e Hemitriccus diops, de acordo com os estudos de Goerck (1999), Leme (2001), Zimmer & Isler (2003), Fitzpatrick (2004), Volpato et al (2006) e Antunes (2007. Destas espécies, apenas H. nattereri e C. lineata apresentaram IPA similar nas trilhas CB1 e CB2; H. diops e S. cinerascens apresentaram valor de IPA maior na trilha CB2 em relação às outras duas e D. rubricollis foi exclusivamente registrada nessa última trilha.…”
Section: Discussionunclassified
“…and observed that richness and abundance increased significantly in areas dominated by bamboo and the most common species were Drymophila rubricollis, Conopophaga lineata, Hylopezus nattereri, Synallaxis cinerascens, and Hemitriccus diops. Many other investigators have recorded associations between these species and the presence of bamboo in the forest (LeMe, 2001;fitzpatriCk, 2004;VoLpato et al, 2006;areta et al, 2009). Bamboo specialists were estimated to comprise 5% of the bird community in the Paraná region (anjoS et al, 2007).…”
Section: Habitat Of Bird Speciesmentioning
confidence: 99%